Peningkatan Kemampuan Membaca dengan Metode Demonstrasi pada Siswa Kelas III SD Negeri Duren Bandungan - Suryaningsih, Yulianti; Karim, Abdul; Puspitasari, Nimas (Faculty of Teacher Training and Education of Undaris, 2023)
This study aims to improve reading skills using the demonstration method for third grade students at Duren Elementary School, Bandungan District, Semarang Regency. The type of research used is classroom action research (PTK). The research subjects were class III students at SD Negeri Duren Bandungan with a total of 25 students in the even semester of the 2022-2023 academic year. Data collection techniques with the performance of students' reading abilities, observing student activities and observing teacher skills during the learning process take place. The results showed that the reading ability of class III students from cycle I increased by 32% to 88% in cycle II. The results of observations of student activity in the conversion of scale 4, namely in the first cycle of 2.11, qualified enough to increase in the second cycle of 3.33 with good qualifications. The results of observations of teacher skills on a scale of 4, the first cycle of 2.11 qualified enough to increase in the second cycle of 2.45 with good qualifications. Based on the results of this study indicate that the use of the demonstration method can improve the reading ability of class III students at SD Negeri Duren Bandungan.Keywords: reading, reading ability, Demonstration Method